Experimental study on effect of wick structures on thermal performance enhancement of cylindrical heat pipes - Kumaresan, G.; Vijayakumar, P.; Ravikumar, M.; Kamatchi, R.; Selvakumar, P. (Journal of thermal analysis and calorimetry, 2019)
The effect of varying wick structures viz. mesh, sintered and composite wick (sintered-mesh) on the thermal enhancement of cylindrical heat pipes is experimentally investigated. In addition, the investigation focused on the effect of inclination angle and heat input of heat pipe. Surfactant free CuO nano-fluid with a mass concentration of 1.0% is used as a working fluid. The energy and exergy analysis of heat pipe was also conducted at various conditions. To analyze the distinctive performance of composite heat pipe, a heat pipe is filled with DI water and the obtained results are compared with nanofluid results. The maximum heat transfer capability of composite heat pipe is improved by 35.71% and 18.75% compared with mesh and sintered wicks. The composite heat pipe with CuO nanofluid as working fluid instead of DI water improves the heat transport capacity by 11.76%. Surface temperature of heat pipe significantly reduces by varying the wick structure viz. mesh, sintered and composite wick. The composite heat pipe with 1.0 mass% of CuO nanofluid obtained 3.7 °C reduction in surface temperature at evaporator section compared with DI water. Thermal resistance of heat pipe is gradually reduces with increasing inclination angle. The maximum reduction is observed for composite wick, sintered and mesh wick heat pipes are 47.50, 43.70 and 24.39% respectively at 45° inclination angle compared with horizontal axis.